1981
DOI: 10.1056/nejm198101083040201
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Serum Cholesterol, and Death from Coronary Heart Disease

Abstract: Over twenty years ago, we evaluated diet, serum cholesterol, and other variables in 1900 middle-aged men and repeated the evaluation one year later. No therapeutic suggestions were made. Vital status was determined at the 20th anniversary of the initial examination. Scores summarizing each participant's dietary intake of cholesterol, saturated fatty acids, and polyunsaturated fatty acids were calculated according to the formulas of Keys and Hegsted and their co-workers. The two scores were highly correlated, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
224
1
15

Year Published

1983
1983
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 659 publications
(260 citation statements)
references
References 28 publications
16
224
1
15
Order By: Relevance
“…The weak association observed between dietary consumption of cholesterol and variation in plasma levels of lipid-lipoprotein produced consistent results according to some studies 31,39 , but contradictory results according to others 41,42 . These findings confirm that, despite high individual variability, the ingestion of cholesterol in the diet has a lower association with serum cholesterol than any other dietary component.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The weak association observed between dietary consumption of cholesterol and variation in plasma levels of lipid-lipoprotein produced consistent results according to some studies 31,39 , but contradictory results according to others 41,42 . These findings confirm that, despite high individual variability, the ingestion of cholesterol in the diet has a lower association with serum cholesterol than any other dietary component.…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, evidence from epidemiological studies suggests that these associations could either not be confirmed 30 or were shown to be only marginally significant 31 .…”
Section: Discussionmentioning
confidence: 98%
“…Dietary cholesterol increased coronary risk in both the IrelandBoston Diet-Heart Study (53) and the Western Electric study (54). These results showed good agreement between the Keys dietary score, which emphasized saturated fat, and the Hegsted score, which emphasized dietary cholesterol.…”
Section: Adverse Effects Of Dietary Cholesterolmentioning
confidence: 84%
“…The most recent report showing that ®sh may protect against CHD death was based on 30 y follow-up data on 1822 males from the Chicago area (Daviglus et al, 1997;Shekelle et al, 1981Shekelle et al, , 1985. The protective effect was not apparent in the crude analysis, but appeared in the multivariate analysis as a signi®cant trend (P 0.04).…”
Section: Fish Consumption and Coronary Heart Disease Mortality P Marcmentioning
confidence: 99%